Work Optimization of Unit 1 Resort Crime Unit in Handling Theft with Weighting under the Jurisdiction of Karanganyar Police Station (Advances in Police Science Research Journal, 2024)
This study aims to optimize the implementation of theft investigation by weighting by unit I Resort Crime Unit of Karanganyar Police Station with the output of case settlement (crime clearance) criminal acts of theft by weighting will increase so that it will have implications for the outcome of creating law enforcement in accordance with procedures. The research approach used in writing this final project uses a qualitative approach. This research is included in the Field Study Research. Sources of data in this study came from primary and secondary data. Data collection techniques used in this study were interviews, observation, and document studies. In determining the validity of the data, research uses data triangulation techniques. The data analysis technique used in this research is a qualitative data analysis technique. The results of this study are the planning, organizing, implementing, and evaluation stages related to disclosing criminal acts of theft with weights that are not yet optimal and the effectiveness of the law in optimizing the disclosure of criminal acts of theft with weights at the Karanganyar Police.
Keywords: kinerja penanganan tindak pidana curat polres karanganyar